A simple turn-on and turn-off angles searching method for copper loss minimization of the switched reluctance motor. Issue 4 (3rd July 2017) - Chen, Hai-Jin; Li, Jin-Yang
Abstract : Purpose: The purpose of this paper is to present a simple and effective method to search the optimal turn-on and turn-off angles on-line for the control of the switched reluctance motor (SRM). The optimal turn-on and turn-off angles are defined as the ones that can meet torque production requirements with minimum copper loss. Design/methodology/approach: The optimal turn-on and turn-off angles are first defined based on the analysis of the SRM losses and torque production principles. Then the algorithm for optimal angles searching is developed, and the searching parameters are determined through analytical computation. The optimal angles are approached on-line with iterative process. Simulation and experiments are finally performed to verify the proposed method. Findings: The presented method can meet torque production requirements while copper loss is minimized. The optimal turn-on and turn-off angles are generally approached within five phase cycles for most of the SRM operation modes. Furthermore, the SRM drive system using the presented method exhibits good dynamics during starting and sudden load operations. Practical implications: The presented method is simple, and implementation of it is easy. It is an eligible candidate for industrial applications where energy conversion efficiency is crucial. Originality/value: The optimal turn-off angle definition that considers both torque production and copper loss minimization is proposed. The turn-on and turn-off angles are searched independently on-line with little SRM geometrical information. The searching steps are derived through analytical computation and qualitative analysis so that both the searching speed and algorithm convergence are balanced.